Long-term results after distal rectus femoris transfer as a part of multilevel surgery for the correction of stiff-knee gait in spastic diplegic cerebral palsy - Dreher, Thomas; Wolf, Sebastian Immanuel; Maier, Michael Wolfgang; Hagmann, Sébastien; Vegvari, Dóra; Gantz, Simone; Heitzmann, Daniel; Wenz, Wolfram; Braatz, Frank (The journal of bone & joint surgery. A, American volume, 2012)
Background: The evidence for distal rectus femoris transfer as a part of multilevel surgery for the correction of stiff-knee gait in children with spastic diplegic cerebral palsy is limited because of inconsistent outcomes reported in various studies and the lack of long-term evaluations. Methods: This study investigated the long-term results (mean, nine years) for fifty-three ambulatory patients with spastic diplegic cerebral palsy and stiff-knee gait treated with standardized distal rectus femoris transfer as a part of multilevel surgery. Standardized three-dimensional gait analysis and clinical examination were carried out before surgery and at one year and nine years after surgery. Patients with decreased peak knee flexion in swing phase who had distal rectus femoris transfer to correct the decreased peak knee flexion in swing phase (C-DRFT) were evaluated separately from those with normal or increased peak knee flexion in swing phase who had distal rectus femoris transfer done as a prophylactic procedure (P-DRFT). Results: A significantly increased peak knee flexion in swing phase was found in the C-DRFT group one year after surgery, while a significant loss (15°) in peak knee flexion in swing phase was noted in the P-DRFT group. A slight but not significant increase in peak knee flexion in swing phase in both groups was noted at the time of the long-term follow-up. A significant improvement in timing of peak knee flexion in swing phase was only found for the C-DRFT group, and was maintained after nine years. Knee motion and knee flexion velocity were significantly increased in both groups and were maintained at long-term follow-up in the C-DRFT group, while the P-DRFT showed a deterioration of knee motion. Conclusions: Distal rectus femoris transfer is an effective procedure to treat stiff-knee gait featuring decreased peak knee flexion in swing phase and leads to a long-lasting increase of peak knee flexion in swing phase nine years after surgery. Patients with more involvement showed a greater potential to benefit from distal rectus femoris transfer. However, 18% of the patients showed a permanently poor response and 15% developed recurrence. In patients with severe knee flexion who underwent a prophylactic distal rectus femoris transfer, a significant loss in peak knee flexion in swing phase was noted and thus a prophylactic distal rectus femoris transfer may not be indicated in these patients. Level of Evidence: Therapeutic Level IV. See Instructions for Authors for a complete description of levels of evidence.